2010
DOI: 10.1016/j.physc.2010.05.138
|View full text |Cite
|
Sign up to set email alerts
|

Flux pinning properties of MgB2 thin films on Ti buffered substrate prepared by molecular beam epitaxy

Abstract: Transport properties of the MgB 2 thin films on Si, MgO and ZnO substrates with Ti buffer layer prepared by molecular beam epitaxy were investigated to clarify effects of the substrates and the Ti buffer layer on flux pinning. The critical current density J c of each sample shows different dependence on magnetic fields parallel to c-axis. However, the scaling analysis of the macroscopic pinning force for all the measured samples implies that the grain boundaries work as the dominant pinning centers for B//c. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Thus we can conclude that the MgO plates are oriented with (0 0 1) MgO planes parallel to (0 0 1) MgB2 MgB 2 planes. This mutual orientation of cubic MgO and hexagonal MgB 2 phases has already been observed and discussed [25][26][27][28][29][30][31]. 1 0 MgO [29].…”
Section: Grains and Inter-grain Secondary Phase Layerssupporting
confidence: 61%
See 1 more Smart Citation
“…Thus we can conclude that the MgO plates are oriented with (0 0 1) MgO planes parallel to (0 0 1) MgB2 MgB 2 planes. This mutual orientation of cubic MgO and hexagonal MgB 2 phases has already been observed and discussed [25][26][27][28][29][30][31]. 1 0 MgO [29].…”
Section: Grains and Inter-grain Secondary Phase Layerssupporting
confidence: 61%
“…The film was polycrystalline and it did not have any preferential in-plane orientation, only strong [0 0 1] MgB2 out-of-plane texture. Some other authors also published c-oriented MgB 2 thin film on (0 0 1) MgO substrate without any additional information about the in-plane orientation[26][27][28]. Tian et al showed clear epitaxial growth of (…”
mentioning
confidence: 99%